STRATEGI PENINGKATAN EFEKTIVITAS PENGELOLAAN DANA DESA - Masbiran, Vivi Ukhwatul Khasanah; Murliasari, Rika; Afriyanni; Wulandari, Sekar Nur (Jurnal Bina Praja, 2021)
This study aims to identify, map, and determine the critical elements of Village Fund management's constraints, needs, and actors using the Interpretative Structural Modeling (ISM) method. ISM is a modeling technique that explains the contextual relationship between elements based on expert opinion to provide a concrete picture of something in a visual map. The results of the study indicate that there are eleven elements of village funds management constraints. In addition, there are seven elements needed to improve the effectiveness of village funds management and eight aspects of DD management actors. Furthermore, based on the ISM analysis results, the main component of managing village funds is limited human resources. In addition, the results obtained that the main determining actors in increasing the effectiveness of village funds management are the Village Government and the Community Empowerment Service. Meanwhile, the critical strategy to improve the effectiveness of Village Fund management is strengthening regulations and policies and strengthening human resource capacity through training and mentoring. This study recommends improving regulations, especially synchronizing the management of village funds starting from the planning and accountability stages, starting from the central government to village governments to implement a strategy to strengthen regulations. Meanwhile, the synergy between the government, the private sector, village communities, and universities increases competence through training and managing village funds.